MAKNA PESAN DAKWAH RIBA PADA PAPAN BILLBOARD DI KOTA PEKANBARU - Muhamad Ilham; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The circulation of dakwah message in early 2016 which contains dakwah message riba is attached on any billboard in pekanbaru city but the contains of message still less understood by the readers. CV.Permata Art is the enterprise who shared the message of dakwah riba. This reasearch is purpose to know the meaning of Representament, Object, and the Interpretant in the message of dakwah riba on the billboard in Pekanbaru city.This research use qualitative method with the analysis presentation of semiothic Charles Sanders Peirce. The Object of this research is the Message of dakwah riba. The Subject of this research are determined three billboard entitled Kredit Riba, ATM Riba and Pelaku Riba ditantang Perang oleh Allah & Rasul. The techniques used for data collection is documentation for determination the location and the actual picture of the billboard. Literature review for reference of the analysis and the interview for support the argmentation of the analysis.Based on the result of this research are found first, meaning of dakwah riba message as Representament is the performer of riba itself. Second, meaning of dakwah riba message as Object is The action for support Pekanbaru city will be a Sunnah City. Third, meaning of dakwah riba message as Interpretant is the performers Riba is sinful who must be repent because they don’t know when the death are coming, if they are still doing their action of riba that is will be Allah and The Prophets not only cursed you but also war against you.Keyword: Mean, performer riba, billboard, representament, object, interpretant.